Prediksi Ketersediaan Air Sebuah DAS Menggunakan Model NAM (Nedbor Afstromnings Model): Studi Kasus di DAS Loning, Magelang, Jawa Tengah = Prediction of Water Availability of A Watershed using NAM (Nedbor Afstromnings Mo - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This study was conducted at Loning watershed in Magelang, Central Java. The NAM model was used to predict the water yield from the watershed and the optimal parameters was obtained using method of least square simulation model. The calibration of the model was done using rainfall and runoff data of 1995 -1996, meanwhile verification of the model was conducted using data of 1997 -2000. The optimal parameters of the NAM model were CQOF = 0,001